Exploring factors that influence the food behaviors of junior enlisted Army family members - Kidd, Tandalayo; Peters, Paula K.; Holcomb, Carol Ann (My University, 2008)
With the stress of the on-going war and soldiers being deployed, the needs of military families have likely increased. Young military families, generally E-4s (Specialists) and below, may suffer even more stress due to lack of experience and life skills. Many families have seen financial difficulties arise as a result of the soldier being deployed. The nutrition and health status of these families may be at risk because of some of the dietary behaviors associated with limited financial resource audiences. Thus, the purpose of this study was to explore factors that influenced the food behaviors of junior enlisted (E-4s and below) Army families.
Keywords: Low-income families; Military families; Qualitative research; Focus groups; Dietary behaviors